Necrolytic erythema migrans in celiac disease - Dassouli Ryme; Hanane BayBay; Souad Choukri; Zakia Douhi; Sara Elloudi; Fatima Zahra Mernissi (Our Dermatology Online, 2022)
Erythema migrans necrolytica is a red, blistering rash that spreads over the skin. It particularly affects the skin around the mouth and distal extremities, but can also be found on the lower abdomen, buttocks, perineum and groin. It is strongly associated with glucagonoma, a glucagon-producing tumor of the pancreas, but is also seen in a number of other conditions, including liver disease and intestinal malabsorption such as celiac disease. We present a case of a patient with a history of poorly followed celiac disease presenting with a clinical picture of ENM. This rare case adds to our understanding of the clinical presentation of NME, as well as highlights the importance of acting in a timely manner to avoid the most redoubtful complications.